School nurses’ experiences of health-promoting work to prevent stress in Swedish adolescents - Persson, Louise; Rahr, Charlotta; Garmy, Pernilla; Einberg, Eva-Lena (Frontiers in Psychology, 2022)
Aim: To investigate school nurses’ experiences of health-promoting work to prevent stress in Swedish adolescents. Method: Swedish school nurses (n=225) responded to a web survey with open-ended questions. The results were subjected to a qualitative content analysis. Results: Six categories were identified from the analysis: (1) Knowledge of body and soul, (2) Identifying stress and ill health, (3) Collaborative working within/outside school, (4) Make yourself (ie. school nurses) visible to the students, (5) Support students' learning, and (6) Tools for stress management. One of the most important themes in preventing and counteracting stress in school-aged children and adolescents was promoting healthy living habits. That school nurses were easily accessible and visible were important for them to identify stress as early as possible. The close collaboration with the school health care team and building relationships with the students were emphasized. The stress in adolescents was largely linked to schoolwork and performance anxiety. To counteract this, the dialogue with the teachers was important to increase their knowledge of mental health problems and stress and influence the scheduling of school exams. Conclusion: The study contributes to increased knowledge in the field and provides concrete strategies for how school nurses can work to counteract stress in students.